The Effect of Feeding Drill Training Method and Coordination Toward Ability of Forehand Groundstroke Depth - Gunarto, Peby (Fakultas Ilmu Keolahragaan Universitas Negeri Malang, 2021)
The purpose of this study was to know about effect of feeding drill Training method toward forehand groundstroke depth, correlation between coordination with ability forehand groundstroke depth, and difference forehand groundstroke depth ability athletes who have high coordination eye-hand with athletes who have low coordination eye-hand. Sampel of this study were twelve male tenis athlete tenis beginner Mandiri Tenis Club Singaraja Bali. To measure coordination used coordination test instrument and to know forehand groundstroke depth ability used groundstroke depth test.Result showed that feeding drill method has effect toward forehand groundstroke depth, there were strong correlation between coordination with ability forehand groundstroke depth athletes who have high and low eye-hand coordination, there were differences ability of forehand groundstroke depth athletes who have high eye-hand coordination with athletes who have low eye-hand coordination.Base on the result of the data analysis, it could be concluded that feeding drill training method could increase the ability of forehand groundstroke depth and the level of coordination to determine the ability of the athlete’s groundstroke depth.